Contrabando – Um Filme Costeiro: comprehensions over the (dis)course of the Uruguay River - Ferreira Dias, Ana Beatriz; Siqueira dos Santos, Lindalva (Revista Letras Raras, 2024)
The objective of this paper is to analyze meanings over the Uruguay River in the script of the film Contrabando - Um Filme Costeiro (2022) [Contraband – A Coastal Film], produced in interior towns of the Brazilian state of Rio Grande do Sul (RS), directed by filmmaker João Pedro Gottardo. This feature film problematizes the lives of riverside dwellers, focusing on the trajectories of chibeiros — people who trade goods from Argentina that will later be sold in Brazil while avoiding import controls and tax collection — as well as their families. The chibeiros, as they are popularly known, cross the river in small boats to look for products in the neighboring country. In the film, the river plays a fundamental role in the construction of the narrative. In order to understand ideological views about the river, the words as ideological signs will be taken as a unit of study. To this end, the theoretical-methodological perspective formulated by the Bakhtin Circle is correlated with the approach to metaphors of Lakoff and Jonhnson (2009). The final considerations point to personification as an evaluative position that, anchored in ambivalence, indicates the river as a figure that knows the power of life and death: on the one hand being able to give life, welcoming it, and narrating it in its mysteries, and on the other hand of taking life away, devouring it through its destructive power. This is a way of introducing meaning and structure to this element of nature, which is so present as a part of the everyday lives of the chibeiros and their families.